2015
DOI: 10.1128/jvi.00773-15
|View full text |Cite
|
Sign up to set email alerts
|

Novel Functions of Hendra Virus G N-Glycans and Comparisons to Nipah Virus

Abstract: Hendra virus (HeV) and Nipah virus (NiV) are reportedly the most deadly pathogens within the Paramyxoviridae family. These two viruses bind the cellular entry receptors ephrin B2 and/or ephrin B3 via the viral attachment glycoprotein G, and the concerted efforts of G and the viral fusion glycoprotein F result in membrane fusion. Membrane fusion is essential for viral entry into host cells and for cell-cell fusion, a hallmark of the disease pathobiology. HeV G is heavily N-glycosylated, but the functions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 51 publications
13
56
0
Order By: Relevance
“…3C), which is expected since F tri is readily secreted and, unlike wt F, is likely not endocytosed for cleavage by cathepsin L (14). These co-IP results confirmed that our flow-cytometric strategies reliably detect protein-protein interactions using complementary approaches and, importantly, that uncleaved F is capable of interacting with G, as previously thought based on co-IP results alone (33)(34)(35)41).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…3C), which is expected since F tri is readily secreted and, unlike wt F, is likely not endocytosed for cleavage by cathepsin L (14). These co-IP results confirmed that our flow-cytometric strategies reliably detect protein-protein interactions using complementary approaches and, importantly, that uncleaved F is capable of interacting with G, as previously thought based on co-IP results alone (33)(34)(35)41).…”
Section: Resultssupporting
confidence: 73%
“…Immunoblotting was performed using mouse anti-AU1 (BioLegend), rabbit anti-HA (Bethyl Laboratories), or mouse anti-FLAG (Sigma) antibody at dilutions of 1:250 to 1:2,000. Fluorescent secondary antibodies were diluted 1:1,000 to 1:2,000, and blots were imaged on a Bio-Rad Chemidoc 249 imager (8,41).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Viruses such as HIV-1, HCV, and Hendra virus exploit N-glycans to shield themselves from the host immune response (23,25,115,116). In a similar way, O-glycans have also been suggested to shield immunodominant epitopes in herpesviruses (91,92).…”
Section: Discussionmentioning
confidence: 94%
“…pJP007 lanes in each blot are lysates from cells transfected with the vector plasmid. Molecular mass marker sizes, in kilodaltons, are indicated on the left sides of panels C to E. Some viral glycoproteins involved in fusion, such as HSV-1 gB and Nipah virus G protein, form oligomers (31,32). To determine whether Ov8 formed oligomers, extracts from cells transfected with pJP007-Ov8 were resolved under native (untreated and native PAGE) conditions, followed by Western blotting (Fig.…”
Section: Resultsmentioning
confidence: 99%